Gamification-Based Learning Content Entitled Disciple in Christian Religious Education and Character Subjects - Sihombing, Samuel Septrian; I Gede Bendesa Subawa; I Nyoman Indhi Wiradika (Jurnal Media dan Teknologi Pendidikan, 2025)
The lack of variety in learning media often leads to a decline in students’ motivation and enthusiasm for learning. This condition makes the learning process feel monotonous as it predominantly relies on presentations and textbooks. This study aims to design and analyze the validity of gamification-based learning content as an innovative alternative medium to support learning. The research employed a development approach using the ADDIE model. The subjects involved were content experts, media experts, and students as product users. The data consisted of both quantitative and qualitative data collected through interviews, document analysis, and questionnaires. Data were analyzed using descriptive quantitative and qualitative techniques. The results revealed that content expert evaluation obtained a score of 100% (excellent), media expert evaluation 100% (excellent), individual trial evaluation 94.66% (excellent), small group trial evaluation 93.11% (excellent), and field trial evaluation 92.05% (excellent). The findings conclude that gamification-based learning content is valid with excellent criteria and feasible for use in the learning process. Thus, the innovation of gamification-based content has implications for optimizing learning quality, particularly in enhancing students’ motivation, engagement, and overall learning experience.